THE IMPORTANCE OF INNOVATIVE TECHNOLOGIES IN SUSTAINABLE DEVELOPMENT - X. I. Isroilov (European Science Publishing, 2023)
Because of concern about the environment in different parts of the world, several concepts such as sustainable development and green growth are emerging. This includes different interpretations of the balance between the ecological, social and economic aspects of our society by different sectors. This article examines the dependence of innovations mainly on natural resources. It will clarify how sustainable development relates to innovative technologies.
Keywords: Sustainable development, economic stability, social stability, sustainable competitiveness, resource efficiency, innovation, Niche technologies, End-of-pipe technologies, resource consumption.